Small Business as the Main Driver of Economic Development - Fayziyevna, Bayzakova Dilbar (Research Parks Publishers, 2023)
This article talks about how to further reform and stabilize small business and private entrepreneurship in the Republic of Uzbekistan, the growth of private enterprises today, and the level of small business potential.